2012
DOI: 10.1111/j.1600-0609.2012.01764.x
|View full text |Cite
|
Sign up to set email alerts
|

The novel, orally bioavailable HSP90 inhibitor NVP‐HSP990 induces cell cycle arrest and apoptosis in multiple myeloma cells and acts synergistically with melphalan by increased cleavage of caspases

Abstract: Heat shock protein 90 (HSP90) binds and stabilizes numerous proteins and kinases essential for myeloma cell survival and proliferation. We and others have recently demonstrated that inhibition of HSP90 by small molecular mass inhibitors induces cell death in multiple myeloma (MM). However, some of the HSP90 inhibitors involved in early clinical trials have shown limited antitumor activity and unfavorable toxicity profiles. Here, we analyzed the effects of the novel, orally bioavailable HSP90 inhibitor NVP-HSP9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…We observed decreases in the Akt levels and cleavage of Bid by BIIB021, followed by the activation of caspase-9. BIIB021 also activated caspase-8 in Molt-4 cells, consistent with the findings of a previous study [39] . Additionally, TPL has been shown to induce the loss of mitochondrial membrane potential and cytochrome c release, whereas caspase-9 knockout cells are resistant to TPL [16] .…”
Section: Discussionsupporting
confidence: 92%
“…We observed decreases in the Akt levels and cleavage of Bid by BIIB021, followed by the activation of caspase-9. BIIB021 also activated caspase-8 in Molt-4 cells, consistent with the findings of a previous study [39] . Additionally, TPL has been shown to induce the loss of mitochondrial membrane potential and cytochrome c release, whereas caspase-9 knockout cells are resistant to TPL [16] .…”
Section: Discussionsupporting
confidence: 92%
“…Lamottke et al (117) demonstrated that inhibition of Hsp90 by small molecular mass inhibitors induced cell death in multiple myeloma. They analyzed the effects of the novel, orally bioavailable Hsp90 inhibitor NVP-Hsp990 on multiple myeloma cell proliferation and survival.…”
Section: Combination Of Hsp90 Inhibitor With Second Therapymentioning
confidence: 99%
“…Additive effects of 17-AAG and SN-38, the active metabolite of IRN, have also been reported in p53-null HCT116 cells (Tse et al 2009). NVP-HSP990 has also shown synergy when used in combination with melphalan in multiple myeloma cells, inducing significantly more apoptosis than that induced by either agent alone (Lamottke et al 2012). …”
Section: Discussionmentioning
confidence: 99%